Incidence and characterization of early- and late-onset skin diseases in neonates – A hospital-based cross-sectional study - Pandya, Nitin; Agrawal, Amit (Indian Journal of Child Health, 2020)
Background: Neonatal skin diseases occur in almost every newborn baby. Many are transient, involute rapidly and require no management. Objective: The objective of the study was to study the incidence and characterization of early and late onset of various skin diseases in the neonates. Methods: A cross-sectional observational study was carried out among 200 neonates in a tertiary care hospital in Central India. Skin lesions which appeared on or before 48 h before birth were categorized as early onset and skin lesion appearing after 48 h were considered as late onset and the characteristics of lesions were highlighted. Results: The most common skin lesions identified within 48 h of birth were Epstein pearl’s (77.0%), followed by Mongolian spot (45.5%), desquamation of skin (35%), sebaceous gland hypertrophy (31.5%), and milia (28.4%), respectively. Less incidence of salmon patch, erythema toxicum neonatorum, impetigo, miliaria rubra, accessory auricles, pigmented nevi, port-wine stain, and lamellar ichthyosis also was recorded. Impetigo (11.2%) and candidiasis (11.2%) were commonly seen after 48 h of birth followed by dermatitis 6.4% and a few cases of birthmarks. Conclusion: Along with increasing awareness of neonatal diseases, our study results also aid in better identification and diagnosis of these diseases.